Land Conversion in Abroorza A. Yusra's Novel Danum: A Study of Literary Ecology - Magvira Ali; Muslimin; Herman Didipu (Raja Zulkarnain Education Foundation, 2026)
Land conversion is a change in land function that impacts the environment and the socio-economic conditions of the community. This study examines the process of land conversion in Abroorza A. Yusra's novel Danum, including land conversion patterns, their impacts, and the resulting social conflicts. The purpose of this study is to describe the land conversion patterns, their impacts, and the social conflicts that arise as a result of this land conversion process. This study uses Literary Ecology theory to examine the relationship between humans and nature, Sihaloho's land conversion theory on the patterns and impacts of land conversion, and Soekanto's social conflict theory as a basis for analyzing the resulting social conflicts. This study uses a descriptive method with data in the form of excerpts from the novel Danum that represent land conversion patterns, their impacts, and the resulting social conflicts. The primary data source is Abroorza A. Yusra's novel Danum, which was examined through literature review. Data analysis was conducted through filtering, thematic grouping, interpretation of meaning, and drawing conclusions. The results of the study show that (1) Abroorza A. Yusra's novel Danum depicts three patterns of land conversion, a planned enclave pattern through collusion of power, a pattern resulting from social and economic pressure, and a pattern of agrarian adaptation to a capitalist economy. (2) This land conversion has three impacts, namely changes in land ownership from indigenous communities to companies, changes in land use that damage the environment in the form of loss of customary forests, and social changes in communities. (3) In addition, three forms of social conflict emerged according to Soekanto, including politics, class, and individuals, which highlight social dynamics, human-nature relationships, and changes in values due to land conversion. Danum displays social complexity, human-nature interactions, and changes in values due to land conversion.